Effect of genomic X-chromosome regions on Nelore bull fertility - Hermisdorff, Isis da Costa; Diaz, Iara Del Pilar Solar; de Camargo, Gregório Miguel Ferreira; de Albuquerque, Lucia Galvão [UNESP]; Costa, Raphael Bermal (Springer Nature, 2021)
Scrotal circumference (SC) is a commonly used trait related to sexual precocity in bulls. Genome-wide association studies have uncovered a lot of genes related to this trait, however, only those present on autosomes. The inclusion of the second biggest chromosome (BTAX) can improve the knowledge of the genetic architecture of this trait. In this study, we performed a weighted, single-step, genome-wide association study using a 777 k BovineHD BeadChip (IllumHD) to analyze the association between SNPs and SC in Brazilian Nelore cattle. Phenotypes from 79,300 males and 3263 genotypes (2017 from females and 1246 from males)—(39,367 SNPs markers located at ChrX) were used. We identified eight regions on chromosome X that displayed important associations with SC. The results showed that together the genomic windows explained 28.52% of the genetic variance for the examined trait. Genes with potential functions in reproduction and fertility regulation were highlighted as candidates for sexual precocity rates in Nelore cattle (AFF2 and PJA1). Moreover, we found 10 genes that had not previously been identified as being associated with sexual precocity traits in cattle. These findings will further advance our understanding of the genetic architecture, considering mainly the presence of the chromosome X, for indicine cattle reproductive traits, being useful in the context of genomic prediction in beef cattle.
Keywords: Bos taurus indicus; Nelore cattle; Scrotal circumference; Sexual chromosomes; Sexual precocity